Health service use and costs for infant behaviour problems and maternal stress. (April 2016) - Le, Ha N D; Gold, Lisa; Mensah, Fiona K; Cook, Fallon; Bayer, Jordana K; Hiscock, Harriet
Abstract : Aim: We aim to describe health service (HS) use in the first 6 months post‐partum and to examine the associations between service costs, infant behaviour and maternal depressive symptoms. Methods: Participants were 781 infants and mothers in Melbourne, Australia. Mothers reported infant feeding, sleeping and crying problems, depressive symptoms and health service use. Costs were valued in 2012 Australian dollars. Results: The most common services used were maternal child health nurses, general practitioners (GP) and allied health. Infant feeding problems were associated with increased costs for services relevant to infant behaviour including maternal child health nurses ( P  = 0.007), GP ( P  = 0.008) and paediatricians ( P  = 0.03). Maternal depressive symptoms were associated with increased costs for services relevant to depressive symptoms including parenting centres ( P  = 0.04), GP ( P  = 0.004), psychiatrists ( P  = 0.02) and psychologists ( P  = 0.001). Mothers who completed high school had higher service costs for infant problems than those with lower education ( P  = 0.02). Single mothers had higher costs for services used for their depressive symptoms than partnered mothers ( P  < 0.001). Mothers with English as a second language had lower service costs for their depressive symptoms ( P  = 0.02). Conclusions: Infant feeding problems and maternal depressive symptoms are associated with higher costs for health services relevant to these conditions. Cost‐effective strategies to manage these conditions are needed with accessibility being ensured for mothers who are experiencing social adversity.